Botanical types and composition of grazing field in the captive breeding area for Timor deer (Cervus timorensis) at Wosu Village, Central Sulawesi. Issue 1 (April 2020) - Arifuddin, M S; Damry,; Najamuddin,; Toknok, B
Abstract: A research has been conducted to determine the botanical types and composition of the grazing field of a captive breeding area for Timor deer ( Cervus timorensis ) at Wosu village, Bungku Barat district, Morowali district, Central Sulawesi province from April 26 to May 16, 2018. Forage samples were taken with a destructive sampling method using a pair of 1 x 1m frame. The dry matter content of the forage samples was analyzed at the animal nutrition and feeding laboratory, Tadulako University. Data were analyzed, and results were presented descriptively. The results showed that the botanical composition of the was 83% kinds of grass and 17% weeds. The grasses were dominated by Imperata cylindrica, Cyperus rotundus, Cyperus kyllingia Endl., and Paspalum conjugatum .